Observing the Effects of Activity Based Learning on Math Comprehension in a High School Algebra Class - Bock, Brandon (My University, 2015)
As a third year high school math teacher, it can be difficult to engage all students with new math concepts. To address this problem, I compared a traditional lecture based class, to classes that emphasized group work, discussions, and demonstrations in front of peers. Activity based teaching methods were the variable used to impact the performance and engagement of participants in three ninth grade Algebra 1 classes. Throughout one ten day long math unit, assessment data was collected and analyzed, and observations of student engagement were documented. The primary emphasis was to identify whether activity based teaching has significant positive effects on students? level of interest, engagement and performance in a 9th grade Algebra 1 class.